Correct-by-Construction Approaches for SoC Design - Sinha, Roopak; Roop, Parthasarathi; Basu, Samik; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This book describes an approach for designing Systems-on-Chip such that the system meets precise mathematical requirements. The methodologies presented enable embedded systems designers to reuse intellectual property (IP) blocks from existing designs in an efficient, reliable manner, automatically generating correct SoCs from multiple, possibly mismatching, components. ·         Provides a single-source reference to correct-by-construction SoC design; ·         Enables optimized design cycles, with techniques to reuse IP blocks reliably; ·         Uses realistic SoC case studies to highlight the concepts introduced;  ·         Demonstrates techniques using industrial standard SoC frameworks such as ARM AMBA.
System-on-A-Chip Design.- The AMBA SOC Platform.- Automatic Verification using Model and Module Checking -- Models for SoCs and Specifications -- SoC Design Methodology -- Automatic Protocol Conversion -- Related Work and Outlook.- Appendix: Converter Generation Algorithm.
Keywords: Electronic circuits; Microprocessors; Electronics; Microelectronics; Circuits and Systems; Processor Architectures; Electronics and Microelectronics, Instrumentation